Pelanggaran Etika Birokrasi dalam Pemerintahan di Indonesia - Lies Kumara Dewi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2021)
In government ethics, there is a prevailing assumption that through the appreciation of good ethics, an apparatus will be able to build a commitment to make himself an example of goodness and maintain government morality. Good government officials and have high morals, will always guard themselves in order to avoid disgraceful acts, because they are called to maintain the mandate given, through imaging the behavior of daily life. Within the scope of the government profession, for example, there are certain values ​​that must be upheld in order to maintain the image of a government capable of carrying out its duties and functions. Trends or symptoms that arise today, many bureaucratic apparatus in carrying out their duties often violate the rules of the game that have been set. Cases related to ethical violations in the government bureaucracy such as corruption and gratification (bribery) involve many professions in violating ethics such as state administration officials, regional heads, legislators, prosecutors, judges, police, tax officials, and so on. Bureaucratic Ethics is part of the rules of the game in the Bureaucracy or Civil Service organization which structurally has regulated the rules of the game, which we know as. Code of Ethics for Civil Servants, which has been regulated by the Civil Service Act. To be more effective in delivering the code of ethics, the code of ethics can be read together -the same on certain occasions which is sometimes followed by a discourse from a ceremonial leader called a ceremonial inspector, the intention is to create favorable moral conditions in experienced organizations and to cultivate the necessary mental attitude, as well as to create good morals. The Code of Ethics is usually read in flag ceremonies, monthly ceremonies or ceremonies anniversary of the organization concerned, and national ceremonies. In order to create a more ethical Bureaucratic Apparatus according to the above expectations, it is necessary to make efforts and training in that direction as well as to enforce strict and clear sanctions for those who violate the code of ethics regardless of their rank and position. Anyone who violates the code of ethics, whether it's superiors or subordinates, must be dealt with firmly to create a deterrent effect. Therefore, in relation to the Code of Ethics for Civil Servants, it must really animate, appreciate and implement the employment rules that have been determined or set as the rules of the game for the Bureaucratic apparatus. Keywords: bureaucratic ethics, government